Limnoperna fortunei (Dunker, 1857) (Mollusca, Bivalvia, Mytilidae): first record in the São Francisco River basin, Brazil - Barbosa, Newton P. U.; Silva, Fabiano A.; De Oliveira, Márcia Divina; Neto, Miguel Arcanjo dos Santos; De Carvalho, Marcela David; Cardoso, Antônio Valadão (Check list (Luís Felipe Toledo), 2016)
Limnoperna fortunei (Dunker, 1857) is a small mytilid native to Southeast Asia. It was introduced in South America in early 1990 and has dispersed from Argentina to central Brazil, and until 2014 has been restricted mainly to the Paraná and Uruguay river basins. The present note reports the occurrence of Limnoperna fortunei for the first time in the São Francisco River basin in northeastern Brazil. The establishment of L. fortunei in these regions will require close attention from the government and also by society.